2019
DOI: 10.1093/jisesa/iez113
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Methoprene-Tolerant Arrests Ovarian Development in the Sogatella furcifera (Hemiptera: Delphacidae)

Abstract: Juvenile hormone (JH) is responsible for repressing larval metamorphosis and inducing vitellogenesis and egg production in insects. Methoprene-tolerant (Met) is known to be an intracellular receptor and transducer of JH. We examined the role of Met in ovarian development in the rice pest Sogatella furcifera (Horváth). We first cloned and sequenced S. furcifera Met (SfMet). The SfMet protein belongs to the basic helix–loop–helix/Per-Arnt-Sim (bHLH-PAS) family with a bHLH domain and two PAS domains (PAS-A and PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Similar results were obtained in many lepidopterans such as G. molesta , C. suppressalis and H. armigera (Ma et al, 2018; Miao et al, 2020; Zhang et al, 2019). Higher expression in adults also suggests its function in reproduction, as in S. furcifera and H. armigera (Hu et al, 2019; Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in many lepidopterans such as G. molesta , C. suppressalis and H. armigera (Ma et al, 2018; Miao et al, 2020; Zhang et al, 2019). Higher expression in adults also suggests its function in reproduction, as in S. furcifera and H. armigera (Hu et al, 2019; Ma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Kr‐h1 plays a crucial role in oocyte maturation and ovarian development (Kayukawa et al ., 2012). In Sogatella furcifera , Met knockdown repressed the Kr‐h1 expression, and regulated the vitellogenesis (Hu et al ., 2019). In contrast, scilencing Met by RNAi could block ovarian development and/or suppress Vg gene expression in T. castaneum (Parthasarathy et al ., 2010), Pyrrhocoris apterus (Smykal et al ., 2014) and Bactrocera dorsalis (Yue et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Methoprene‐tolerant (Met), a member of the bHLH‐PAS (basic helix–loop–helix‐Per‐Arnt‐Sim) transcription factor family, is considered as the JH intranuclear receptor in insects such as Drosophila melanogaster (Jindra et al ., 2013). Some studies have revealed that as a universal JH receptor, Met regulates insect development and reproduction, and is involved in vitellogenesis and oogenesis (Guo et al ., 2014; Villallobos‐Sambucaro et al ., 2015; Hu et al ., 2019). Krüppel homologue 1 ( Kr‐h1 ), as an early JH‐response gene downstream of Met, plays a key role in maintaining larval or nymphal status and in promoting adult reproduction (Belles and Santos, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of either Met or Kr‐h1 resulted in reduced Vg expression and impeded ovarian development with lowered fecundity in B. dorsalis (Yue et al ., 2018). Similar findings have also been reported in Sogatella furcifera , Nilaparvata lugens and the red flour beetle, T. castaneum (Lin et al ., 2015; Jiang et al ., 2017; Hu et al ., 2019, 2020; Naruse et al ., 2020). Sheng et al .…”
Section: Discussionmentioning
confidence: 99%